Ion Migration: A "Double‐Edged Sword" for Halide‐Perovskite‐Based Electronic Devices. Issue 5 (28th November 2019) - Zhang, Teng; Hu, Chen; Yang, Shihe
Abstract: Ion migration has been regarded as one of the most interesting and mysterious processes in halide‐perovskite‐based electronic devices. On the one hand, ion migration contributes to the hysteresis and poor stability problems of perovskite devices. On the other hand, the mobile ions can passivate the interfaces of perovskite devices, leading to improved carrier transportation and collection. This article gives a critical review on the ion migration in halide perovskite materials. It starts with a brief introduction of the origin and nature of the ion migration problem in perovskite materials. Next, the electric, photoelectric, and structural phenomena resulting from ion migration and their influence on the performance and stability of the perovskite devices are focused on. The recent literature work on the characterization of ion migration is reviewed and the characterization techniques are highlighted. Furthermore, different approaches that can suppress the ion migration process are also introduced. Finally, ion migration in the emerging all‐inorganic halide perovskite materials is compared with that in hybrid halide perovskite materials, and the implications on device design and performance are discussed. Abstract : Ion migration is common in halide perovskite materials and plays a key role in their applications. This review introduces ion migration originated phenomena and their influence on material and device properties, and discusses characterization techniques, prevention, and utilization of ion migration. Finally, prospects of future studies on ion migration, especially the ion migration in all‐inorganic perovskite materials, are provided.